Os Parques Areião e Vaca Brava na mitigação das ilhas de calor na cidade de Goiânia (GO) - Silva, Keyla Vaz (2017)
The present research was developed in the city of Goiânia-GO with the objective of analyzing the importance of the Areião and Vaca Brava Parks in the mitigation of heat islands, from the spatial and temporal variation of temperature and relative humidity of the air and Absolute minimum, considering different forms of land use and occupation. The analysis considered the parameters temperature and relative humidity of the maximum and minimum air; Morphometric aspects, such as slope, hypsometry, orientation of the slopes; The different patterns of land use and occupation; The regional circulation. The morphometric information was obtained from the digital cartographic base model of the Urban Basic Digital Map of Goiânia (MUBDG, version 23) using ArcGis 10.1 software. The soil use and occupation pattern was obtained from the orthophoto image. The theoretical and methodological proposal was structured in the S.C.U (Urban Climate System), based on the Monteiro thermodynamic perception channel (1976). Air temperature and humidity data were obtained in situ and by means of secondary data provided by INMET (National Institute of Meteorology) from May to December 2016. In situ data were obtained from thermocouples (Datalogger) installed in (Sezarino and Monteiro, 1990b), with records every 15 minutes, distributed in densely urbanized sites and parks (Areião and Vaca Brava). The study area is located in the southern portion of Goiânia, due to the peculiar characteristics of a metropolis city. This research allowed to understand the spatial and temporal variation of the temperature and relative humidity of the air, being that the aspect of the seasonality is strongly identified. Among the analyzed factors, the morphometry, in this scale of analysis, had little influence on the spatial variation of the data. The pattern of land use and occupation was what, together with the regional dynamics, established influences in the analysis of data behavior. Specifically, points P3 and P4 (Field Headquarters of Goiás Esporte Clube and State College Pedro Xavier Teixeira) presented higher values of maximum air temperature (38.8 and 39.8 ° C) and the lowest relative humidity Air, of 18%. The importance of points P1 and P2 (Areião and Vaca Brava parks) is emphasized for cooling the temperature and increasing the humidity of the air in the place. They presented during the period considered hotter and drier in the study area, contribution of up to 5,5ºC in the cooling of the air temperature and, of up to 7%, in the higher humidity, thus improving the environmental quality. It is considered that due to the strong climatic seasonality of Goiânia, it is necessary to expand green areas as corridors integrated with the city parks in order to make it possible to cool the effects of the heat island.